2014
DOI: 10.1080/02791072.2014.962715
|View full text |Cite
|
Sign up to set email alerts
|

Significant Life Events and their Impact on Alcohol and Drug Use: A Qualitative Study

Abstract: This study used a life-course perspective to identify and understand life events related to long-term alcohol and other drug (AOD) use trajectories across the life span. Using a purposive sample, we conducted semi-structured telephone interviews with 48 participants (n=30 abstinent and 18 non-abstinent) from a longitudinal study of AOD outcomes 15 years following outpatient AOD treatment. A content analysis was conducted using ATLAS.ti software to identify events and salient themes. Caregiving for an ill or de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 52 publications
(53 reference statements)
0
24
0
Order By: Relevance
“…In the former case, some succeeded in staying abstinent, but most were fighting against the craving and the temptation to start using again with some relapsing. Causality, of course, could not be demonstrated, but it is well known that life events such as COVID-19 epidemic can lead to relapse (Jessup et al, 2014;McCabe, et al, 2016;Pilowsky, Keyes, Geier, Grant, & Hasin, 2013). Our four patients in a stable recovery managed to stay abstinent.…”
Section: Discussionmentioning
confidence: 73%
“…In the former case, some succeeded in staying abstinent, but most were fighting against the craving and the temptation to start using again with some relapsing. Causality, of course, could not be demonstrated, but it is well known that life events such as COVID-19 epidemic can lead to relapse (Jessup et al, 2014;McCabe, et al, 2016;Pilowsky, Keyes, Geier, Grant, & Hasin, 2013). Our four patients in a stable recovery managed to stay abstinent.…”
Section: Discussionmentioning
confidence: 73%
“…Qualitative studies have revealed that the expectant mother's willingness to do her best for the unborn child facilitates smoking cessation in pregnancy [40]. In addition, altruistic caregiving has been found to be the most significant life experience promoting abstinence in the context of addictions [41]. In the recent comprehensive review and meta-analysis maternal-fetal attachment was not yet recognized as a predictor of smoking cessation during pregnancy [16].…”
Section: Discussionmentioning
confidence: 99%
“…Pregnancy is a specific and potential time for significant changes in attitudes and values in an individual's life. Often, the safety and well‐being of her infant may provide a strong motivation for a woman to work toward abstinence (Crozier et al., ; Jessup et al., ; Pajulo, Suchman, Kalland, & Mayes, ) and provides an especially well‐grounded phase for intervention. On the other hand, the pregnancy of substance‐abusing mothers is usually unplanned (Heil et al., ; Strengell et al., 2014), and pregnancy also can be a period of increased fear, anxiety, and guilt regarding the health of the child.…”
Section: Theorymentioning
confidence: 99%